Geomagnetic activity and the North Atlantic Oscillation - Bucha, V. (Václav) (Studia Geophysica et Geodaetica, 2014)
The North Atlantic Oscillation (NAO) is the prominent pattern of winter climate variability that has a strong effect on weather in the North Atlantic region and the adjacent continents. At present, uncertainty prevails as to the mechanisms controlling the variability of the NAO. It is also difficult to explain why the positive phase of the NAO has prevailed over the past 37 years (1972-2008). We found high positive correlation coefficients between geomagnetic activity (used as a measure of solar wind intensity) and the NAO indices that equal 0.76 for 1962-1994 and 0.63 for 1961-2011. Positive correlations of the distribution of surface air temperature with the NAO and similarly with geomagnetic activity occur in the Northern Hemisphere. These results encourage our search for possible causes controlling the NAO.